2016–2017 Seasonal Influenza Vaccine Availability at Urgent Care Centers in the state of Arizona, USA. (4th October 2017) - Beatty, Norman; Hager, Kelly; Mckeown, Kyle; Mora, Francisco; Matthias, Kathryn; Nix, David; Al Mohajer, Mayar
Abstract: Background: Urgent Care Centers (UCCs) routinely treat episodic conditions requiring immediate but not emergent attention. They offer health care on a walk-in basis in urbanized and convenient locations, with extended business hours. Nationwide statistics estimated more than 7, 000 operating UCCs throughout the United States in 2016. Methods: Utilizing public information, we gathered a list of all operating UCCs in the state of Arizona. Following IRB approval, we conducted a cross-sectional phone survey from January 25 th to February 13 th, 2017. We assessed whether the 2016–2017 seasonal influenza vaccination was being offered at these facilities. If the vaccine was offered, we further collected data on ages of administration, costs of vaccination, and availability. Results: A total of 193/217 (88.9%) facilities met our inclusion criteria to be deemed an operating UCC. The 2016–2017 seasonal influenza vaccination was offered at 155/193 (80.3%) of UCCs in Arizona. None of the 6 pediatric-only UCCs provided the vaccine. Among facilities that offered influenza vaccination, 20/155 (12.9%) only vaccinated adults at least 18 years of age, 13 (8.4%) vaccinated adults and children 12 years and older, 47 (30.3%) vaccinated adults and children 4 years and older, and 57 (36.8%) vaccinated adults and children 6-months or older (Table 1). During the surveyed period, influenza vaccination was out of stock in 46/155 (29.7%) facilities; with 28/46 (60.9%) of those facilities having no plans to re-order more. Only 9/155 (6.2%) UCCs billed medical insurance to cover the cost of influenza vaccination. Out-of-pocket costs per a single vaccine ranged from 20–80 USD (mean 26.10 USD). Conclusion: To our knowledge, this is the first study to assess whether the seasonal influenza vaccine is being administered at UCCs. Our results indicated major inconsistences among UCCs in Arizona to offer influenza vaccination to the populations they serve, particularly children. Urgent care medicine is now playing an important role in our evolving and expanding health care system, with many people relying on UCCs for their primary health care needs. Efforts are needed to implement strategies to improve influenza vaccination across all ages in this sector. Further studies are warranted to assess seasonal influenza vaccination practices among UCCs nationwide. Disclosures: All authors: No reported disclosures.